Analysis of Physical Indicators on The Diversity of Water Microorganisms in The Batang Hari River, Metro - Fajar, Rahmad; Narsan, Vifty Octanarlia; Sari, Tika Mayang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The diversity of aquatic microorganisms was an important component in aquatic ecosystems, because they play a crucial role in biogeochemical cycles and ecological balance. These microorganisms can reflect the condition of the aquatic evirontment and be an indicator of ecosystem health. On the other hand, the physiscal conditions of water such as temperature, pH, and brightness greatly influence the presence and activity of these microorganisms. This research used survey and consecutive sampling methods. Sampling was carried out at two stations, namely in the upstream section located in Sumber Sari village, South Metro Ditrict, Metro City and in the downstream section located in Banjarrejo Village, Batanghari District, East Lampung Regency. The results of research carried out on the Way Batnghari tributary obtained and average temperature value of 29,5ºC in the upstream section and average temperature value of 28,6ºC in the downstream section. In terms of brightness, the upstream section has a better brightness with a value of 25 cm compared to the downstream section which has a lower brightness of 20 cm. The pH value in the downstream section is 6,7 slightly more acidic than the upstream section which has a normal pH level of 7,2. The diversity index of microorganisms in the Way Batanghari Metro tributary obtained a diversity index of 1,24 in the medium category. This value shows that the Way Batanghari tributary is included in the moderatelly polluted category.